Evaluation of Music Performance Anxiety in Portuguese Classical Musicians - Mourão de Carvalho e Damas, Carlos Alexandre (2019)
Music performance anxiety is a problem that affects musicians, potentially generating psychological and physiological symptoms that may sometimes be debilitating, and in many situations interfering with the quality of their performances. The present study aims to quantitativelyanalyze the levels of music performance anxiety of classical music teachers, singers and instrumentalists who are professionally active either on mainland Portugal and or in its autonomous regions. We carried out aquestionnaire survey in which professional musicians and students (n=188) participated voluntarily. The results revealed that 86.7% of the musicians reported suffering from this problem. Respondents also reported recourse to drugs, alcohol and psychotropic substances to deal with the problem. We conclude that music performance anxiety afflicts most musicians and that it would be highly pertinent to carry out further research in order to better grasp the extent and depth of this problem.